2016
DOI: 10.1186/s40064-016-2555-0
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology guided by ultrasound in the diagnosis of subcentimetre thyroid nodules

Abstract: BackgroundThis study aimed to investigate the value of fine needle aspiration biopsy (FNAB) under ultrasound guidance in diagnosis of thyroid nodules. In a retrospective analysis of FNAB in 1050 cases of patients with 1100 nodules, patients were divided according to the maximum diameter of their nodules into two groups: >1.0 and ≤1.0 cm. The ultrasound-guided FNAB cytology results were compared between two groups.ResultsUltrasound findings showed that among 1100 thyroid nodules, 547 were highly suspicious, 358… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Regarding the sensitivity and specificity of U/S in diagnosing nodule malignancy, this study agrees with Neagoe (2017) who suggested that cervical ultrasound has a sensitivity of 92.3% and specificity of 75.3%. These results also agree with Li et al (2016) who stated that the U/S diagnosis of thyroid nodules had an overall sensitivity of 86.0% and a specificity of 81.9%. Neagoe (2017) showed that FNAC had a sensitivity of 33.3% and specificity of 93.3%.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the sensitivity and specificity of U/S in diagnosing nodule malignancy, this study agrees with Neagoe (2017) who suggested that cervical ultrasound has a sensitivity of 92.3% and specificity of 75.3%. These results also agree with Li et al (2016) who stated that the U/S diagnosis of thyroid nodules had an overall sensitivity of 86.0% and a specificity of 81.9%. Neagoe (2017) showed that FNAC had a sensitivity of 33.3% and specificity of 93.3%.…”
Section: Discussionsupporting
confidence: 92%
“…Although some studies have demonstrated that US-FNA is a useful tool for subcentimeter nodules with good diagnostic accuracy [9,20,21], the rates of nondiagnostic FNA results were highly variable and ranged between 0.4% and 17.7% [9,[20][21][22][23][24]. ND means that the slide prepared by US-FNA contains inadequate or unsatisfactory contents that can be interpreted by cytopathologists.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 Histologically, TGDCs are composed of squamous cells. 7 Here, a 65-year-old patient was admitted to the hospital for treatment of thyroid nodes. Fine needle aspiration results showed good differentiation of squamous cells.…”
Section: Discussionmentioning
confidence: 99%
“…8 Fine needle aspiration does not accurately distinguish follicular adenoma from well-differentiated follicular carcinoma or hyperplastic nodules in the NG. 7 Moreover, the possibility of a nodule developing into a TGDC carcinoma is less than 1%. The vast majority of TGDC carcinomas are papillary carcinomas, and only a small number of TGDC carcinomas are squamous cell or follicular carcinomas.…”
Section: Discussionmentioning
confidence: 99%